Revitalisasi Pendidikan Karakter Untuk Mencetak Generasi Unggul - Abuddin (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
The article explores the need to revitalize character education for Indonesian future generation. It proposes that revitalizing character education is done through four points. The first is implementing holistic character-based instruction. Social, emotional, cognitive, physical, moral, and spiritual theories apply in this instruction. Second, included in the character education are moral, value, and religion education as well as civil society. Third, character education in this instance should revitalize the roles of family, schools, and society. It means that character education is the responsibility of the three parties. Fourth, revitalization of mass media is also of paramount importance since, even though mass media function as entertainment, information, and education, the first two are more dominant. It is for this reason that mass media should also contribute to this revitalization.